2023
DOI: 10.1261/rna.079498.122
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the potential of chemically modified peptide nucleic acids for RNA-based therapeutics

Abstract: RNA therapeutics have emerged as next-generation therapy for the treatment of many diseases. Unlike small molecules, RNA targeted drugs are not limited by the availability of binding pockets on the protein, but rather utilize Watson crick (WC) base pairing rules to recognize the target RNA and modulate gene expression. Antisense oligonucleotides (ASOs) present a powerful therapeutic approach to treat disorders triggered by genetic alterations. ASOs recognize the cognate site on the target RNA to alter gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 90 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…A critical aspect of the PNA design involves ensuring the uniqueness of the target site. However, owing to the short length of PNAs, full or partial complementary matches with genome regions other than the target gene occur frequently 26 . Our comprehensive genome-wide search revealed that the 10-bp anti- groEL PNA exhibited no sequence matching with any Buchnera genes, except the target groEL , at their translational start codons or Shine-Dalgarno regions.…”
Section: Resultsmentioning
confidence: 99%
“…A critical aspect of the PNA design involves ensuring the uniqueness of the target site. However, owing to the short length of PNAs, full or partial complementary matches with genome regions other than the target gene occur frequently 26 . Our comprehensive genome-wide search revealed that the 10-bp anti- groEL PNA exhibited no sequence matching with any Buchnera genes, except the target groEL , at their translational start codons or Shine-Dalgarno regions.…”
Section: Resultsmentioning
confidence: 99%
“…A critical aspect of the PNA design involves ensuring the uniqueness of the target site. However, owing to the short length of PNAs, full or partial complementary matches with genome regions other than the target gene occur frequently[24]. Our comprehensive genome-wide search revealed that the 10-bp anti- groEL PNA exhibited no sequence matching with any Buchnera genes, except the target groEL , at their translational start codons or Shine-Dalgarno regions.…”
Section: Resultsmentioning
confidence: 99%
“…This chemical structure also confers resistance toward nucleases and proteases. Like PMOs, PNAs are uncharged, leading to strong binding to complementary sequences, but they face a cellular delivery barrier (Pradeep et al , 2023 ). Other chemical modifications that increase the affinity of oligonucleotides for their targets and thereby improve potency and selectivity center on 2′ ribose modifications, such as 2′‐ O ‐methyl (2′‐ O ‐Me), 2′‐ O ‐methoxyethyl (2′ MOE), and 2′‐fluoro (2′‐F; Kulkarni et al , 2021 ).…”
Section: Rna ‐Based Therapeutic Strategiesmentioning
confidence: 99%